Molybdenum potential vital role in plants metabolism for optimizing the growth and development - Muhammad Shoaib Rana; Parashuram Bhantana; Muhammad Imran; Muhammad Hamzah Saleem; Mohamed G Moussa; Zaid Khan; Imran Khan; Mufid Alam; Muhammad Abbas; Rana Binyamin; Javaria Afzal; Muhamad Syaifudin; et al. (Annals of Environmental Science and Toxicology - Peertechz Publications, 2020)
Molybdenum importance for appropriate plant functioning and growth is inconsistent by the most of the plants in respect to the total quantity that is obligatory for them. Molybdenum is a micronutrient that is directly involved in the metabolic functions of nitrogen in the plant. The transition metal molybdenum, in molybdate form, is essential for plants as a number of enzymes use it to catalyze most important reactions in the nitrogen acclimatization, the synthesis of the phytohormone, degradation of the purine and the detoxification of the sulfite. There are more than known 50 different enzymes that need Mo, whether direct or indirect impacts on plant growth and development, primarily phytohormones and the N-metabolism involving processes. On the other hand, in the synthesis of ABA uniquely Moco is involved, there on the level of ABA Moco effect is highly vital and ultimately by the response in the stress and the stomatal control, it has a very important role in the rate of transpiration and water relations. The practices that are involved in the fertilization of Mo optimization in crops, has a very important scope in discovering and improving these practices where the legumes are fixing the N or No3- is primarily source of available N. The deficiency of Mo and to enhance the molybdoenzymes activity, it may be very effective and vital important to use the spray of Mo as foliar application through the soil. The most recent understanding that from the soil how the plant gets access Mo or how they redistribute it is not still clear. However in the system f prokaryotes, it has been found that in plants it has likewise physiological Mo transport phenotypes. So, the mechanism of transport of Mo in the prokaryotes is needed as well as the reconsideration of anion transport mechanism that is in plants, will provide a help to solve that how this is accumulated. In this review, the discussion covers about the vital importance of Mo to enhance the productivity for optimizing the yield concentrating on metabolism, uptake, transport, storage, Mo cofactors, application, focusing on some other recent constrains in the recent situation of agriculture, where the yield and development in agriculture may be aided by increasing the Mo nutrition.